Tratamiento ortodóncico de mordidas profundas (2011)
ABSTRACT: Adequate vertical overbite is an important purpose of the orthodontic treatment, in terms of the achievement of esthetic goals (tooth display) as well as functional, stable and long-lasting occlusal relations. Development of excessive vertical overbite is known as deep bite, and it is usually found in some maxillomandibular discrepancies, as in Angle Class II division 2 malocclusions. Deep bite orthodontic correction or camouflage can be achieved by means of biomechanics of posterior teeth extrusion, anterior teeth intrusion, and/or incisors labialization. Choosing the right mechanics depends on the patient’s specific facial, occlusal and functional characteristics. The purpose of this review is to summarize the aspects associated to the diagnosis and orthodontic treatment of deep bite.